2010
DOI: 10.1002/jbt.20348
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in paraquat‐mediated toxicity: A review

Abstract: Paraquat, a cationic herbicide, produces degenerative lesions in the lung and in the nervous system after systemic administration to man and animals. Many cases of acute poisoning and death have been reported over the past few decades. Although a definitive mechanism of toxicity of paraquat has not been delineated, a cyclic single electron reduction/oxidation is a critical mechanistic event. The redox cycling of paraquat has two potentially important consequences relevant to the development of toxicity: the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 80 publications
1
42
0
1
Order By: Relevance
“…Studies have proved that PQ induced reactive oxygen species induce the expression of nitric oxide synthase (NOS) (Morán et al, 2010). PQ induced lung injury could be inhibited by using NOS inhibitors as nitric oxide (NO) play a crucial role in PQ toxicity (Mustafa et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proved that PQ induced reactive oxygen species induce the expression of nitric oxide synthase (NOS) (Morán et al, 2010). PQ induced lung injury could be inhibited by using NOS inhibitors as nitric oxide (NO) play a crucial role in PQ toxicity (Mustafa et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Among different herbicides, Paraquat (1,1'-dimethyl-4,4'-bipyridinium, PQ) is the most widely used herbicide in the world because of its greater efficiency and low cost (Qian et al 2009a;Moran et al 2010). It blocks photosynthesis by accepting electrons from photosystem I (PSI) and causes overproduction of reactive oxygen species (ROS) which caused alteration of the main biomolecule classes, leads to structural and func-1120 A.…”
Section: Introductionmentioning
confidence: 99%
“…It blocks photosynthesis by accepting electrons from photosystem I (PSI) and causes overproduction of reactive oxygen species (ROS) which caused alteration of the main biomolecule classes, leads to structural and func-1120 A. Sood et al tional changes in lipids, proteins, chlorophylls, and nucleic acids (Qian et al 2009a;Moran et al 2010;Sood et al 2011). Holst et al (1982 observed that bipyridilium and phenolic herbicides were detrimental to A. mexicana, causing up to 75% reduction in N 2 fixation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PQ can be deoxidated to form free radicals using elec trons supplied by NADPH; the deoxidated PQ then reacts with molecular oxygen to form O2 -and bipyri dine cations. O2 -is used to produce hydrogen perox ide through the action of superoxide dismutase (SOD); O2 -can also form hydroxyl radicals and other more toxic ROS, thereby inducing an imbalance in the ox idationantioxidant response and generating lung in jury 1,23 . Our data showed that the proportion of O2 -cells was significantly higher in the PQ group than in the control group, while the proportion of O2 -cells was significantly lower at each time point in the APN group than in the PQ group (P<0.01).…”
Section: Discussionmentioning
confidence: 99%